The Effect of Using Brainstorming Technique on the Essay Writing and Self- regulation Learning of the Iraqi Secondary Students (Journal Of Educational and Psychological Researches, 2018)
This study investigated the effect of using brainstorming as a teaching technique on the students’ performance in writing different kinds of essays and self regulation among the secondary students. The total population of this study, consisted of (51) female students of the 5th Secondary grade in Al –kawarzmi School in Erbil during the academic year 2015-2016. The chosen sample consisted of 40 female students, has been divided into two groups. Each one consists of (20) students to represent the experimental group and the control one. Brainstorming technique is used to teach the experimental group, and the conventional method is used to teach the control group. The study instruments used for collecting the data are an essay writing test and Academic Self-regulated Learning Scale. The performance on an essay writing task and Academic Self-regulated Learning Scale has been taken into account as the pretest and posttest in both groups. The validity and reliability of the study instruments are acceptable. T-test formula is used to analyze the data collected. The analysis results show that the experimental group's performance and self- regulation are significantly higher than the performance and self regulation of the control group at (0.05) level of significance. Therefore, the brainstorming teaching technique significantly affects the students’ performance in writing essays and self- regulation.